The effect of fitness dance for elderly on stature/arm span ratio of non-trained old women in Y ogyakarta - M. Mansyur Romi, Santosa Budiharjo Djoko Prakosa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Aging process causes changes of the body composition, body posture, and physical performance. In elderly people, the decrease in muscle mass, muscle strength, and flexibility of body segments reduce the maximum height at the upright standing position.Objectives: This study was aimed to find out the effects of fitness dance for elderly (FDE) on stature/arm span ratio of non-trained old women in Yogyakarta.Methods: Pretest and posttest control design was used. The samples consisted of 30 non-trained healthy old women of Yogyakarta, aged 60-70 years. They were classified into three groups, each consisted of 10 women, namely: Group I (GI) was given FDE 3 days a week. Group II (Gill was given FDE 2 days a week, and non-treatment control group (CG). FDE is a low impact aerobic exercise, created by Association of Indonesian Sports Women, Yogyakarta Branch. The FDE in this research wasthe D series (low impact aerobic). The treatment was performed for 8 weeks, 40-54 minutes in each session. The intensity of exercise was maintained at 70-79% of maximal heart rate by controlling the musical beat. Before and after treatment (in the 2nd, 4th, 6th, 8th week), the subjects were measured using the stature and arm length anthropometry. This study was conducted in April-June 2003 at Kotagede, Yogyakarta.Results: The one way variance analysis among groups revealed that the ratio of stature/arm span was significantly improved (p